Improving the technology of replacing window frames in precast concrete walls - Pashynskyi, Victor; Dzhyrma, Stanislav; Pashynskyi, Mykola; Nastoiashchyi, Vladyslav (Academic journal Industrial Machine Building Civil Engineering, 2022)
The constructive-technological decision of the junction design of a block frame window to an uninsulated precast concrete wall which practically excludes a possibility of condensate formation on a surface of internal window jamb is proved. The study was performed by constructing two-dimensional temperature fields in nodes of different designs and comparing the lowest temperature on the internal window jamb surface with the dew point temperature. It is established that thermal reliability can be ensured by the condensate formation criterion by insulating the exterior window jamb with mineral wool or expanded polystyrene slabs and local facade insulation in the form of an outside window casing with 50 mm thickness and 200…250 mm width. The block frame window should be installed at a distance of 60… 80 mm from the outer surface of the precast concrete wall.
Keywords: condensate; precast concrete walls; temperature regime; thermal failure; window-wall junction